Guanabenz inhibits alveolar bone resorption in a rat model of periodontitis - Ryujiro Muramatsu; Takuma Sato; Kazunori Hamamura; Ken Miyazawa; Atsushi Takeguchi; Masako Tabuchi; Akifumi Togari; Shigemi Goto (Elsevier, 2021)
Increase of sympathetic activity has been known to exacerbate osteoporosis through promotion of bone resorption. However, it is largely unknown about involvement of sympathetic activity in exacerbation of periodontitis. In this study, we investigated whether α2-adrenergic receptor (α2-AR) agonist guanabenz which decreases sympathetic activity, attenuates alveolar bone resorption in rats having high sympathetic activity with periodontitis. Volumes of residual alveolar bone and attachment levels in periodontium were examined using micro-computed tomography and hematoxylin-eosin staining, respectively. Furthermore, osteoclast numbers per bone surface and osteoclast surface per bone surface were measured using tartrate-resistant acid phosphatase staining. To examine the suppressive effects of guanabenz on pro-inflammatory cytokines, expression levels of tyrosine hydroxylase (TH), TNF-α, IL1-β, and IL-6 in periodontium were measured using immunohistostaining. Administration of guanabenz attenuated loss of alveolar bone and attachment levels in rats having high sympathetic activity. Furthermore, its administration suppressed osteoclast numbers in rats having high sympathetic activity. TH, TNF-α, IL-1β, and IL-6 positive cells in periodontium in rats treated with guanabenz for 12 weeks, were lower than those in control rats having high sympathetic activity. This study demonstrated administration of α2-AR agonist guanabenz attenuates alveolar bone resorption through decrease of sympathetic activity in rats.